2011
DOI: 10.5194/acp-11-5347-2011
|View full text |Cite
|
Sign up to set email alerts
|

Modelling light scattering by mineral dust using spheroids: assessment of applicability

Abstract: Abstract.We study the applicability of spheroidal model particles for simulating the single-scattering optical properties of mineral dust aerosols. To assess the range of validity of this model, calculations are compared to laboratory observations for five different dust samples at two wavelengths. We further investigate whether the best-fit shape distributions of spheroids for different mineral dust samples have any similarities that would allow us to suggest a generic first-guess shape distribution for suspe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
101
0
3

Year Published

2012
2012
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(108 citation statements)
references
References 39 publications
4
101
0
3
Order By: Relevance
“…The sensitivity of Q abs,scat,ext to shape confirms the limited range of applicability of spheroids over different types and sizes of mineral dust aerosols, in agreement with previous modeling studies (Merikallio et al, 2011;Hansell Jr. et al, 2011;Otto et al, 2011). Extended studies on the sensitivity to shape of mineral dust particle optical properties in the UV-NIR range can provide useful constrains on the envelope of values to be expected during measurements in ambient air (i.e., Sokolik and Toon, 1999;Hansell Jr. et al, 2011).…”
Section: Optical Properties Of Mineral Dustsupporting
confidence: 66%
See 1 more Smart Citation
“…The sensitivity of Q abs,scat,ext to shape confirms the limited range of applicability of spheroids over different types and sizes of mineral dust aerosols, in agreement with previous modeling studies (Merikallio et al, 2011;Hansell Jr. et al, 2011;Otto et al, 2011). Extended studies on the sensitivity to shape of mineral dust particle optical properties in the UV-NIR range can provide useful constrains on the envelope of values to be expected during measurements in ambient air (i.e., Sokolik and Toon, 1999;Hansell Jr. et al, 2011).…”
Section: Optical Properties Of Mineral Dustsupporting
confidence: 66%
“…The large variability is attributed to the mineral dust particles' variability in size distributions, chemical composition and morphology. Furthermore, different modeling studies on light interaction with mineral dust aerosol show (i) the limited range of applicability, over different types of mineral dust aerosols, of commonly used shapes such as spheres (adopted in Mie computations) and spheroids (adopted in T-matrix computations and in AERONET retrieval) (Merikallio et al, 2011), (ii) the inability of Mie simulations to accurately reproduce the magnitude and wavelength peak positions of the mass absorption/extinction coefficients common for angularly shaped particles (as shown by Hansell Jr. et al (2011) in the infrared region), and (iii) the effect of non-spherical dust particles on the total RF (radiative forcing) is 55/5 % (ocean/land) at the TOA and 15 % at the bottom of the atmosphere (BOA) for both land and ocean, while local radiative heating within a dust plume causes enhancements of 20 % of RF (Otto et al, 2011).…”
Section: B V Scarnato Et Al: Optical Properties Internally Mixed Mmentioning
confidence: 99%
“…By using a distribution of particle aspect ratios, the radiative properties of particles have been more effectively modeled in aerosol retrieval algorithms (Haapanala et al 2012). Many studies have found that incorporating the shape distribution with a large range of aspect ratios has improved models, but lack a physical reason for their choice of aspect ratios (Kahnert 2004;Nousiainen et al 2006;Merikallio et al 2011). Hudson et al (2008) found that incorporating the shape of clay mineral particles (e.g., disc/needle) improves the agreement between models and laboratory results.…”
Section: Introductionmentioning
confidence: 99%
“…The CALIPSO product defines dust as aerosol layers with depolarization ratios greater than 0.2 at 0.532 µm for aerosols that are not located over snow, ice, or tundra, so we use this constraint as well. We consider this to be a relatively conservative constraint for the AERONET lidar ratios, since Merikallio et al (2011) found the depolarization ratio of spheroids to be biased low of measured values for several dust samples. Additionally, we require the aerosol fine mode volume fraction (fvf) to be less than 0.05 for the "pure" dust of this section.…”
Section: Aeronet Lidar Ratios For "Pure" Dustmentioning
confidence: 99%
“…It is also possible that the AERONET refractive indices do not represent true climatological values for dust, and that the regional variability of the AERONET refractive indices are an artifact of irregular shapes or roughness affecting the retrieval. Spheroids (and spheres) are simplifications of the myriad of complex shapes associated with aeolian dust, after all, and the savvy reader will be interested in the ongoing discourse on this topic (Nousiainen, 2009;Merikallio et al, 2011). For instance, the spheroid particles used in the AERONET retrievals are smooth, and do not account for surface roughness effects that can alter extinction efficiency, backscattering enhancement, and depolarization ratios (Nousiainen, 2009;Redmond et al, 2010).…”
Section: Mineralogy Of Dust In the Dust Beltmentioning
confidence: 99%